Diseño e implementación de un prototipo para generación de energía térmica mediante la utilización de materia orgánica de coco como combustible - Flores Jiménez, Bryan Héctor (2019)
Coconut palm production in Ecuador has been growing in the great majority and therefore the accumulation of organic coconut garbage in junk dumps, streets and even at sea has increased. This technological proposal was developed in order to implement a sample for thermal energy generation through the use of coconut organic matter as fuel, to encourage the use of renewable energy sources such as biomass and reduce pollution from the use of fuel fossils, with the use of coconut biomass pellets reduces the emission of greenhouse gases that are produced in the degradation of coconut biomass and generates neutral carbon dioxide, which when emitted into the environment does not produce pollution. The model is composed of a storage hopper that is assembled to a gear motor, which is coupled to an endless screw that is responsible for transporting the pellets to the burner feed, where they fall by gravity to a combustion compartment in which a high power ceramic resistor is housed and is subjected to an air flow produced by a forced draft fan, which at the time of work causes combustion to be generated while creating a flame with a high temperature that is brought to the boiler home to produce saturated steam. According to the thermochemical and thermodynamic analysis that was carried out, it was obtained that the higher calorific value of coconut biomass is 19.1 MJ / kg and that the lower calorific value is 15.5 MJ / kg. According with these results and the use that the model was done, the calculation methodology was applied, taking into account the working parameters of the boiler that are: producing saturated steam at 63 ° C with a pressure of 80 PSI, to obtain these levels of heat and pressure it was calculated that an amount of coconut biomass of 176,371kg is required.